Sound touch elastography for assessing cirrhosis preoperatively in infants with biliary atresia: Comparison with serum fibrosis biomarkers - Duan, Xingxing; Yang, Liu; Wen, Rong; Cao, Hong; Wen, Huan; Liu, Wengang; Yuan, Hongxia (Frontiers in Pediatrics, 2022)
Introduction: At present, it is very important for children with biliary atresia (BA) to accurately assess the stages of hepatic fibrosis before performing Kasai portoenterostomy (KPE). Some studies demonstrated that ultrasound elastography can be used to assess the stages of hepatic fibrosis by detecting liver stiffness.Therefore, the aim of this work was to explore the usefulness of sound touch elastography (STE) in preoperatively assessing liver cirrhosis in infants with BA. Methods: A total of 189 children from Hunan Children's Hospital with highly suspected BA were selected in this study, and their preoperative liver STE values and related clinical data were collected. The pathological results of the liver stages were considered as the gold standard, Spearman correlation was used to analyze the correlation between each parameter and the stage of hepatic fibrosis, and the ROC curve was used to analyze the diagnostic performance for cirrhosis of each parameter. Results: Among the selected 189 patients with suspected BA, 159 were included in this study and were composed of 3 with hepatic fibrosis stage F1, 45 at stage F2, 41 at stage F3, and 70 at stage F4, while no patients at stage F0 were present. Spearman correlation analysis showed that the liver STE value had the highest correlation with the stage of hepatic fibrosis, with a correlation coefficient of 0.813 (P<0.001). The liver STE value had the highest diagnostic performance for hepatic cirrhosis compared to the other serum fibrosis biomarkers; the area under the ROC curve was 0.899 when the best cut-off value was 14.57 kPa. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were 78.6%, 84.3%, 79.7%, 83.3% and 81.8%, respectively. Conclusion: The liver STE value has a high correlation with the stage of hepatic fibrosis in children with BA. STE has a good diagnostic performance in evaluating the cirrhosis before Kasai portoenterostomy in children with BA.